Topical Cyclosporine in Treatment of Post-LASIK Symptomatic Dry Eye: Doi:10.36351/pjo.v36i4.1078 - Iqbal, Muhammad Saeed; Latif, Kanwal (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the role of 0.05% topical cyclosporine A (CsA) in treatment of symptomatic dry eye after LASIK (Laser-Assisted in Situ Keratomileusis). Study Design: Interventional Case Series. Place and Duration of Study: Ophthalmology Department, Sir Syed Hospital, Karachi, from July 2018 to Dec. 2019. Methods: Seventy-five patients who underwent LASIK for myopic refractive error and presented with symptomatic dry eye and showed no response to artificial tears therapy after 1 month of LASIK were selected. The patient had ablation zone diameter of 6mm and flap diameter was 8.5mm to 9mm. Cyclisporine A 0.05% ophthalmic preparation was added to treatment regimen and response was observed at 1, 3 and 6 months. OSDI (Ocular Surface Disease Index) scores, Tear film break up time (TBUT), Schirmer’s test (ST) values and Best Corrected Visual Acuity (BCVA) were recorded to analyze the treatment response at each visit. The statistical interpretation was done by using SPSS version 21. To interpret the correlation between pre-treatment and 6 month post treatment, Paired sample T test was applied with 95% Confidence Interval; CI and p-value of ? 0.05. Results: The mean post-LASIK OSDI score of enrolled patients was 54.25 ± 10.81. After 6 months of treatment mean OSDI score was improved to 21.05 ± 5.13 (p < 0.001). Post-LASIK mean ST value was 5.2 ± 1.2 mm and mean TBUT value was 5.6 ± 1.3 seconds, which changed to 9.8 ± 1.0 mm and 8.9 ± 1.1 seconds respectively. BCVA improved from Log MAR 0.14 ± 0.09 to 0.01 ± 0.03 (p < 0.001). Conclusion: Topical CsA 0.05% was effective in alleviating the symptoms of post-LASIK dry eye. Key Words: LASIK, Dry eye, Ocular Surface Disease Index Score, Cyclosporine A.